Merging Structural and Process–Related Approaches to the Study of Agreeableness: A Preregistered Replication and Extension Attempt. Issue 2 (March 2020) - Vize, Colin E.; Lynam, Donald R.
Agreeableness is one of the major domains included within prominent hierarchical models of personality like the five–factor model. (Low) agreeableness is the strongest correlate of a variety of antisocial behaviours relative to the other five–factor model domains. Although there is substantial evidence that (low) agreeableness is arguably the most important personality correlate of various antisocial behaviours, this evidence is descriptive and provides little information on the direction or processes underlying the relation. Process–related research has started to provide more insight into how agreeableness–related traits give rise to various antisocial and prosocial behaviours. The proposed study looked to first replicate previous research on some of the potential cognitive–emotional processes related to agreeableness and then conduct exploratory analyses to identify which, if any, of the empirically identified facets of agreeableness bear specific relations to the processes under study. Overall, we were unable to replicate the primary effects of interest in regard to processes of agreeableness and found little support for our preregistered confirmatory and exploratory hypotheses despite having high power (≥.94) to detect these effects. Nonetheless, process models of personality remain at the vanguard of personality research, and we discuss how the current results can inform future work in this area. © 2020 European Association of Personality Psychology